Easy CCTV - Zeng, Glenn Zhaosong (2015)
Easy CCTV is a project on home security for the unique housing environment of Singapore. This project will be approached in two different parts. Part A will consist of the business plan and market analysis, while Part B will focus on the technical aspects and challenges of implementing the system. Easy CCTV is a new take on Singapore home security demand focusing on a niche market.